Xylem water flow in a crack willow tree (Salix fragilis L.) in relation to diurnal changes of environment - Čermák, Jan; Jeník, Jan; Kučera, Jiří; Žídek, Vladimír (Oecologia, 1984)
The diurnal course of the xylem water flow in a solitary Salix fragilis L. tree in a wet grassland was measured using the tissue heat-balance method. There was considerable variation due to meteorological factors. Maximum flow rate was 0.4 kg h-1 m-2 of crown projection area, or 5.9 kg h-1 kg-1 leaf dry weight. The daily total was 2.4 kg m-2 day-1 or 36 kg kg-1 day-1. Water flow decreased immediately at the tree base and at the branches after start of rain, and in a branch, after cutting it off: the time constant of the system was 600-700 s in both cases. The part of the crown oriented to the sun transpired up to ten times as much as the shaded part. Over 70% of the total cross-sectional area of the conductive xylem vessels of the trunk was used by the transpiration flow. The water content of the trunk tracked the diurnal changes of the xylem water flow rate with a short time-lag. During the day, 1% of the trunk volume was temporarily exploited as water reserve, an amount equalling 3% of daily water loss. The stereometric configuration of the crown significantly influenced its water loss. During the summer period, about 33 mature (polycormic) trees per ha may drain 100% of water consumed by the present-day sedge-grass marsh.